ASSERTIVENESS TRAINING CAN INCREASE NURSING STUDENT CONFIDENCE - Dayat Trihadi; Etlidawati Silvi; Dwi Kania Murtiasih (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Background and purpose : Students to have the confidence to face these challenges. One of the efforts to boost confidence is with assertiveness training. This therapy is done in five sessions with the method of describing, modeling, role play, feedback, and transferring. This study aims to determine the influence of assertiveness training in increasing Nursing student confidence of Nursing Health Science in Muhammadiyah University of Purwokerto.Methods : This study uses quasi experiments method with pretest-posttest design with control group with statistical tests namely Dependent (Paired) and test Independent Samples T test. Sampling technique uses Cluster Random Sampling. Samples in this study were 41 students of S-1 nursing as the intervention group and the other 41 students as control group.Results : The results of the study showed a significant different increase statistically confidence of the students in the intervention group and control group after the intervention group is given assertiveness training ( = 0,000).Conclusion and recomendation : The conclusion of this research is assertiveness training can increase students confidence. The results of the study can be input for health workers, especially nurses to improve the ability to provide nursing actions, as a counselor, and as an educator.